2022
DOI: 10.3390/su14094918
|View full text |Cite
|
Sign up to set email alerts
|

Calcium-Rich Pigeonpea Seed Coat: A Potential Byproduct for Food and Pharmaceutical Industries

Abstract: Pigeonpea is a protein-rich legume which is consumed worldwide in a variety of forms (whole seed, dhal, and as a green vegetable). In India, pigeonpea is milled to yield dhal (cotyledon) and this process generates 25–35% waste byproducts. The hull (seed coat) which accounts for 10% of the byproduct is disposed of either as waste or low-cost cattle feed. To recycle the waste byproducts into the food value chain, this study was conducted with the objectives: (i) to estimate nutrient accumulation in the major see… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 41 publications
1
6
0
Order By: Relevance
“…The variability observed for whole-grain protein in the present study (23.35-29.50%) was higher than the protein content (16.76-26.82%) reported in previous studies (Amarteifio et al, 2002;Sekhon et al, 2017;Obala, 2018;Cheboi et al, 2019;Choi et al, 2020;Jawalekar et al, 2020) and is comparable with the dhal protein content of high protein lines (27-29%; Saxena et al, 1987). The protein content in dhal is higher than that in the whole grain (Susmitha et al, 2022), signifying that dhal nutritional analysis of the superior accessions in this study may still have higher protein than the high protein lines reported by Saxena et al (1987). This indicated the availability of superior parental sources for protein biofortification.…”
Section: Discussionsupporting
confidence: 53%
See 4 more Smart Citations
“…The variability observed for whole-grain protein in the present study (23.35-29.50%) was higher than the protein content (16.76-26.82%) reported in previous studies (Amarteifio et al, 2002;Sekhon et al, 2017;Obala, 2018;Cheboi et al, 2019;Choi et al, 2020;Jawalekar et al, 2020) and is comparable with the dhal protein content of high protein lines (27-29%; Saxena et al, 1987). The protein content in dhal is higher than that in the whole grain (Susmitha et al, 2022), signifying that dhal nutritional analysis of the superior accessions in this study may still have higher protein than the high protein lines reported by Saxena et al (1987). This indicated the availability of superior parental sources for protein biofortification.…”
Section: Discussionsupporting
confidence: 53%
“…The pigeonpea is found to be rich in calcium (Saxena et al, 2010;Susmitha et al, 2022), and the results of this study inferred that the Ca content in pigeonpea (154. 28 mg/100 g) was found to be higher than many staple cereals (7.49-39.36 mg/100 g), such as rice, wheat, maize, pearl millet, sorghum, and barley but lesser to Ca-dense finger millet (364 mg/100 g).…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations